Sox10 cooperates with the mediator subunit 12 during terminal differentiation of myelinating glia - Vogl, Michael; Reiprich, Simone; Küspert, Melanie; Kosian, Thomas; Schrewe, Heinrich; Nave, Klaus-Armin; Wegner, Michael (The Journal of Neuroscience, 2013)
Several transcription factors are essential for terminal differentiation of myelinating glia, among them the high-mobility-group-domain-containing protein Sox10. To better understand how these factors exert their effects and shape glial expression programs, we identified and characterized a physical and functional link between Sox10 and the Med12 subunit of the Mediator complex that serves as a conserved multiprotein interphase between transcription factors and the general transcription machinery. We found that Sox10 bound with two of its conserved domains to the C-terminal region of Med12 and its close relative, Med12-like. In contrast to Med12-like, substantial amounts of Med12 were detected in both Schwann cells and oligodendrocytes. Its conditional glia-specific deletion in mice led to terminal differentiation defects that were highly reminiscent of those obtained after Sox10 deletion. In support of a functional cooperation, both proteins were jointly required for Krox20 induction and were physically associated with the critical regulatory region of the Krox20 gene in myelinating Schwann cells. We conclude that Sox10 functions during terminal differentiation of myelinating glia, at least in part by Med12-dependent recruitment of the Mediator complex.
EVALuna2:4941

The transcription factors Sox10 and Myrf define an essential regulatory network module in differentiating oligodendrocytes - Hornig, Julia; Fröb, Franziska; Vogl, Michael; Hermans-Borgmeyer, Irm; Tamm, Ernst R.; Wegner, Michael (PLoS Genetics, 2013)
Myelin is essential for rapid saltatory conduction and is produced by Schwann cells in the peripheral nervous system and oligodendrocytes in the central nervous system. In both cell types the transcription factor Sox10 is an essential component of the myelin-specific regulatory network. Here we identify Myrf as an oligodendrocyte-specific target of Sox10 and map a Sox10 responsive enhancer to an evolutionarily conserved element in intron 1 of the Myrf gene. Once induced, Myrf cooperates with Sox10 to implement the myelination program as evident from the physical interaction between both proteins and the synergistic activation of several myelin-specific genes. This is strongly reminiscent of the situation in Schwann cells where Sox10 first induces and then cooperates with Krox20 during myelination. Our analyses indicate that the regulatory network for myelination in oligodendrocytes is organized along similar general principles as the one in Schwann cells, but is differentially implemented.
EVALuna2:4940